Precision of image-guided spinal stereotactic ablative radiotherapy and impact of positioning variables. (April 2022) - Billiet, Charlotte; Vingerhoed, Wim; Van Laere, Steven; Joye, Ines; Mercier, Carole; Dirix, Piet; Nevens, Daan; Vermeulen, Peter; Meijnders, Paul; Verellen, Dirk
Abstract: Background and purpose: Spinal stereotactic ablative body radiotherapy (SABR) requires high precision. We evaluate the intrafraction motion during cone-beam computed tomography (CBCT) guided SABR with different immobilization techniques. Material and methods: Fifty-seven consecutive patients were treated for 62 spinal lesions with SABR with positioning corrected in six degrees of freedom. A surface monitoring system was used for patient set up and to ensure patient immobilization in 65% of patients. Intrafractional motion was defined as the difference between the last CBCT before the start of treatment and the first CT afterwards. Results: For all 194 fractions, the mean intrafractional motion was 0.1 cm (0–1.1 cm) in vertical direction, 0.1 cm (0–1.1 cm) in longitudinal direction and 0.1 cm (0–0.5 cm) in lateral direction. A mean pitch of 0.6° (0–4.3°), a roll of 0.5° (0–3.4°) and a rotational motion of 0.4° (0–3.9°) was observed. 95.5% of the translational errors and 95.4% of the rotational errors were within safety range. There was a significantly higher rotational motion for patients with arms along the body (p = 0.01) and without the use of the body mask (p = 0.05). For cervical locations a higher rotational motion was seen, although not significant (p = 0.1). The acquisition of an extra CBCT was correlated with a higher rotational (pitch) motion (p = 0 < 0.01). Conclusion: Very high precision in CBCT guided and surface-guided spinal SABR was observed in this cohort. The lowest intrafraction motion was seen in patients treated with arms above their head and a body mask. The use of IGRT with surface monitoring is an added value for patient monitoring leading to treatment interruption if necessary.